Nodulating white lupins take advantage of the reciprocal interplay between N and P nutritional responses. Issue 1 (10th January 2022) - Buoso, Sara; Zamboni, Anita; Franco, Alessandro; Commisso, Mauro; Guzzo, Flavia; Varanini, Zeno; Pinton, Roberto; Tomasi, Nicola; Zanin, Laura
Abstract: The low bioavailability of nutrients, especially nitrogen (N) and phosphorus (P), is one of the most limiting factors for crop production. In this study, under N‐ and P‐free nutrient solution (−N−P), nodulating white lupin plants developed some nodules and analogous cluster root structures characterized by different morphological, physiological, and molecular responses than those observed upon single nutrient deficiency (strong acidification of external media, a better nutritional status than −N+P and +N−P plants). The multi‐elemental analysis highlighted that the concentrations of nutrients in white lupin plants were mainly affected by P availability. Gene‐expression analyses provided evidence of interconnections between N and P nutritional pathways that are active to promote N and P balance in plants. The root exudome was mainly characterized by N availability in nutrient solution, and, in particular, the absence of N and P in the nutrient solution triggered a high release of phenolic compounds, nucleosides monophosphate and saponines by roots. These morphological, physiological, and molecular responses result from a close interplay between N and P nutritional pathways. They contribute to the good development of nodulating white lupin plants when grown on N‐ and P‐free media. This study provides evidence that limited N and P availability in the nutrient solution can promote white lupin‐ Bradyrhizobium symbiosis, which is favourable for the sustainability of legume production.